Key Drivers of ERP Implementation in Digital Transformation: Evidence from Austro-Ecuadorian - Juan Llivisaca-Villazhañay; Pablo Flores-Siguenza; Rodrigo Guamán; Cristian Urdiales; Ángel M. Gento-Municio (Administrative Sciences)
This study identifies key drivers for ERP implementation in small- and medium-sized enterprises (SMEs) in Austro–Ecuador and examines their impact on operational efficiency, strategic adaptability, and digital transformation. Motivated by the limited empirical evidence on ERP adoption in Latin American SMEs, this research aims to provide Austro–Ecuadorian insights that contribute to innovation management practices in emerging economies. To identify the critical success factors (CSFs) influencing ERP implementation, a four-phase methodology was employed, encompassing a CSF literature review, data collection and case analysis from 55 SMEs, multiple correspondence analysis (MCA), and descriptive ERP analysis. Statistical analysis of the surveyed SMEs, primarily from manufacturing sectors, revealed that while a significant portion (37%) lacked ERP experience, 22.9% were in the process of implementing or actively using systems such as Oracle’s J.D. Edwards Enterprise One and SAP. The MCA highlighted ERP system configuration, vendor relationships, and user training as significant factors for successful ERP implementation, reported by 54.5% of the companies. Quadrant analysis further emphasized the influence of IT structure and legacy systems on implementation characteristics, with cluster analysis identifying three distinct groups of companies based on their ERP strategies. The findings underscore the importance of top management support, business process re-engineering, and external consultants for successful ERP adoption in SMEs, providing practical insights for optimizing innovation management in the digital era. Future research should investigate the long-term impacts of ERP systems on organizational performance and innovation sustainability.